Comparison of the Effectiveness of Pharmacological and Non-Pharmacological Methods in Reducing the Pain of Retinopathy of Prematurity Examination - Khoshnoud Shariati, Maryam; Dastanjani Farahani , Afsar; Taslimi Taleghani, Naeemeh; Palizban, Farzaneh; Naseh, Ali; Maddah, Marzieh; Hajipour , Mahmoud; Razi, Hamed (Novelty in Biomedicine, 2024)
Background: Retinopathy of prematurity (ROP) is one of the common complications in premature neonates. ROP examination is one of the most important examinations for premature babies, which is associated with pain and can be very annoying. This study aimed to compare the effectiveness of pharmacological and non-pharmacological methods in reducing the pain of ROP examination. Materials and Methods: This study was conducted as a double-blind, randomized control trial on 300 ROP examinations of patients who were hospitalized in the NICU department of Mahdieh Hospital in Tehran. The neonates were randomly selected into three groups, and ketamine 2mg/kg nasally, fentanyl two µg/kg nasally10minutes before an examination, and acetaminophen 2drop/kg orally 30 minutes before each examination were given to each neonate as two pharmacological groups. In the non-pharmacological group, infants received saddling-pacifier oral sucrose 25% 0.5cc 2 minutes before examination. Pain was assessed based on PIPP (premature infant pain index). Results: The amount of pain after using oral sucrose was significantly lower than the ketamine-acetaminophen (P-value=0.011) and fentanyl-acetaminophen (P-value=0.027) groups, but there was not a statistically significant difference between the two groups of ketamine-acetaminophen and fentanyl-acetaminophen (P-value=0.953). The hypoxia was more prevalent in the ketamine-acetaminophen group (18.8%), and the least hypoxia occurred in the oral sucrose treatment group (7%) (P-value=0.028). Conclusion: It is concluded that the effect of non-pharmacological drugs is greater than pharmacological drugs in reducing the pain of neonates during ROP examination. The effect of oral sucrose in reducing pain was more significant than ketamine-acetaminophen and fentanyl-acetaminophen. However, there was no significant difference between the two groups of ketamine-acetaminophen and fentanyl-acetaminophen.